THE GRAMMATICAL CATEGORY OF NUMBER AND ITS FUNCTIONS - Aralbay Abatov; N. Yuldashev (Educational Research in Universal Sciences, 2023)
It is certainly vital for communicating in any languages, humans are in need of all parts of speech, though one of the most indispensable parts is noun. Nouns are the most numerous class of words. This article is devoted to give information about the grammatical category of number and its functions.